DETERMINATION OF LAND PROCUREMENT OBJECTS AND ITS IMPLICATIONS FOR THE CALCULATION OF COMPENSATION FOR BRIDGE CONSTRUCTION - Septina, Yola (Universitas Negeri Semarang, 2024)
Land procurement for bridge construction is part of the government's efforts to improve community welfare, in accordance with Article 33 paragraph (3) of the 1945 Constitution and regulated in Law Number 2 of 2012 concerning Land Acquisition. This procurement goes through 4 (four) stages, namely planning, preparation, implementation and delivery of results, but the implementation stage often encounters obstacles, such as changes in land objects. Cases of changes in land area involving watersheds (DAS) which are not part of the procurement object, affect the calculation of compensation. This research aims to analyze the determination of land acquisition objects and its implications for calculating compensation for development. The research results show that the determination of land acquisition objects is based on the Location Determination from the Governor, the Land Plot Map from Task Force A, and the Nominative List from Task Force B. Changes in land area due to watersheds have implications for calculating compensation for land owners. Based on Gustav Radbruch's theory of legal certainty and Walt W. Rostow's development theory, the construction of this bridge plays an important role in encouraging economic growth.